2021
DOI: 10.3390/nu14010054
|View full text |Cite
|
Sign up to set email alerts
|

Eating Slowly Is Associated with Undernutrition among Community-Dwelling Adult Men and Older Adult Women

Abstract: The double burden of malnutrition refers to the co-occurrence of overweight and obesity and undernutrition. Eating quickly has been linked to overweight and obesity. However, no study has examined the association between eating speed and undernutrition. This retrospective, cross-sectional study analyzed data from 3529 community-dwelling residents. Eating speed was divided into three categories: fast, medium, and slow. Undernutrition was defined as body mass index (BMI) of <18.5 kg/m2 in adults aged < 70 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 40 publications
2
6
0
1
Order By: Relevance
“…The present study also reported that slow–speed eating was related to poor nutrition ( 17 ). By contrast, fast eating speed is related to obesity, T2DM, and NAFLD ( 14 16 ).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The present study also reported that slow–speed eating was related to poor nutrition ( 17 ). By contrast, fast eating speed is related to obesity, T2DM, and NAFLD ( 14 16 ).…”
Section: Discussionsupporting
confidence: 78%
“…Eating speed is also important because fast eating is associated with obesity ( 14 ), non–alcoholic fatty liver disease (NAFLD) ( 15 ), and T2DM ( 16 ); therefore, slow eating speed may be effective for lowering obesity risk. On the contrary, slow eating increases the risk of undernutrition ( 17 ). It is because slow speed eating increases anorexigenic gut hormones such as peptide YY and glucagon–like peptide−1 (GLP−1) ( 18 , 19 ) and diet–induced thermogenesis ( 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier research has revealed that eating speed is strongly connected to body weight: fast eating is often tied to a high BMI and its associated comorbidities [18,23,[26][27][28][29], whereas slow eating is related to a lean weight status [30]. Reasons for this phenomenon are not entirely clear, although it is feasible that fast eating engenders greater energy intake [31], whereas slow eating does the opposite [32].…”
Section: Discussionmentioning
confidence: 99%
“…The sample sizes of the reviewed studies varied greatly, ranging from 10 (50) to 197 825 (51) participants. Similarly, participants from various age groups were included, with age ranging from 4 years (52,53) to 87 (54) years. Most studies (n = 76; 73%) included adults between 18 and 65 years old, a number of studies (n = 21; 20%) (7,43,46,47,52,53,(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69) explicitly explored eating rate among children or adolescents, and seven studies (8,11,22,44,54,70,71) (7%) investigated older adults.…”
Section: General Study Characteristicsmentioning
confidence: 99%